Singlet fission in pentacene dimers - Zirzlmeier, Johannes; Lehnherr, Dan; Brana Coto, Pedro; Chernick, Erin; Casillas, Ruben; Basel, Bettina; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Singlet fission (SF) has the potential to supersede the traditional solar energy conversion scheme by means of boosting the photon-to-current conversion efficiencies beyond the 30% Shockley-Queisser limit. Here, we show unambiguous and compelling evidence for unprecedented intramolecular SF within regioisomeric pentacene dimers in room-temperature solutions, with observed triplet quantum yields reaching as high as 156 ± 5%. Whereas previous studies have shown that the collision of a photoexcited chromophore with a ground-state chromophore can give rise to SF, here we demonstrate that the proximity and sufficient coupling through bond or space in pentacene dimers is enough to induce intramolecular SF where two triplets are generated on one molecule.